Fatal secondary septic peritonitis associated with multiple renal and splenic infarcts in Lhasa Apso dog - P.C. Prabu; K. Nagarajan; Ganne Venkata Sudhakar Rao (Indian Journal of Veterinary and Animal Sciences Research, 2025)
An eight year old male Lhasa Apso dog was presented for necropsy with the history of persistent vomition, anorexia, lethargy, dehydration and abdominal distension. Blood picture revealed marked neutrophilic leukocytosis along with left shift. Necropsy examination revealed the presence of secondary septic peritonitis and multiple renal / splenic infarcts. Histologically, perforative/haemorrhagic enteritis, renal infarcts with diffuse glomerular / tubular necrosis of coagulative type and splenic infarction with occluded artery containing bacterial thromboemboli were confirmed. Secondary peritonitis has been observed to be a frequent complication associated with perforation of the intestine. These fatal complications of septic peritonitis present a therapeutic challenge and needs prompt veterinary care and treatment.